2020
DOI: 10.3897/bdj.8.e52233
|View full text |Cite
|
Sign up to set email alerts
|

New insights from museum specimens: a case of Viviparidae (Caenogastropoda: Mollusca) in Iwakawa’s collection preserved in the National Museum of Nature and Science, Tokyo

Abstract: In this study, we clarify the classification of museum specimens of the family Viviparidae, which is composed of six species/subspecies in Japan, including three endangered species. We examined Viviparus sclateri specimens from the Tomotaro Iwakawa collection (1855-1933) in the National Museum of Nature and Science, Tokyo. The Iwakawa's collection was catalogued in 1919 and Viviparus sclateri, labelled with Naga-tanishi, the current Japanese name for H. longispira, which was, at the time, equivalent to Vivipar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 495 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…6A and C). In previous studies on the morphology of the skull in the Japanese wolf, the frontal bone did not largely protrude to the dorsal direction and the slope of the stop was gentle [17,21,37,39,44] (Fig. 6A).…”
Section: Ratio Of Braincase and Frontal Sinus Volumes To Skull Volumementioning
confidence: 84%
See 2 more Smart Citations
“…6A and C). In previous studies on the morphology of the skull in the Japanese wolf, the frontal bone did not largely protrude to the dorsal direction and the slope of the stop was gentle [17,21,37,39,44] (Fig. 6A).…”
Section: Ratio Of Braincase and Frontal Sinus Volumes To Skull Volumementioning
confidence: 84%
“…yielded the same result. Regarding the morphological characteristics of the tympanic cavity in the Japanese wolf, it has been reported that it is shorter in diameter and width than that in Korean wolves [44], and Japanese wolves have ventrally flat tympanic cavities compared with other wild wolves (Fig. 8) [1,42,51].…”
Section: Tympanic Cavity Volume and Tympanic Cavity Volume Ratio To S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, exotic freshwater gastropods have invaded ecosystems through multiple introduction vectors, including deliberate introductions and accidental anthropogenic transfer (Padilla & Williams, 2004). One such invader, the Japanese mystery snail ( Heterogen japonica , synonym Cipangopaludina japonica ; Saito & Kagawa, 2020), was intentionally transported from Japan to North America in c . 1911 to be cultivated for human consumption (Clench & Fuller, 1965; Prashad, 1928), but is now found in tributaries throughout North America (Jokinen, 1982; USGS, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, exotic freshwater gastropods have invaded ecosystems through multiple introduction vectors, including deliberate introductions and accidental anthropogenic transfer (Padilla & Williams, 2004). One such invader, the Japanese mystery snail (Heterogen japonica, synonym Cipangopaludina japonica; Saito & Kagawa, 2020), was intentionally transported from Japan to North America in c. 1911 to be cultivated for human consumption (Clench & Fuller, 1965;Prashad, 1928), but is now found in tributaries throughout North America (Jokinen, 1982;USGS, 2021). Due to its feeding habits (i.e., filter feeder and detritivore), Heterogen japonica can improve overall water quality and productivity in invaded freshwater systems (Solomon et al, 2010;Van Bocxlaer & Strong, 2016); however, it can also negatively impact indigenous snail populations, partly due to exponential population growth in invaded systems (Johnson et al, 2009;Wolfert & Hiltunen, 1968).…”
Section: Introductionmentioning
confidence: 99%